Zinc finger and SCAN domain containing 1, ZSCAN1, is a novel stemness-related tumor suppressor and transcriptional repressor in breast cancer targeting TAZ - Chu, Jian; Li, Yunzhe; He, Misi; Zhang, Hui; Yang, Lingling; Yang, Muyao; Liu, Jingshu; Cui, Chenxi; Hong, Liquan; Hu, Xingchi; Zhou, Lei; Li, Tangya; et al. (Frontiers in Oncology, 2023)
Cancer stem cells (CSCs) targeted therapy holds potential for improving cancer management. In this study, we identified a novel breast cancer (BC) stemness-related tumor suppressor and transcriptional suppressor, Zinc Finger and SCAN Domain Containing 1 (ZSCAN1). ZSCAN1 is aberrantly downregulated in BC tissues and this suppression predicts poor prognosis. Ectopic expression of ZSCAN1 inhibited the proliferation, clonogenicity, and tumorigenicity of BC cells, indicating the tumor suppressor role of ZSCAN1. By employing spheroid-derived CD44+CD24- cells as breast cancer stem cells (BCSCs) model, we found that ZSCAN1-overexpressing BCSCs exhibited weakened stemness properties versus control BCSCs. Oppositely, normal human mammary epithelial (HMLE) cells with ZSCAN1 depletion exhibited enhanced stemness properties, which indicated the stemness inhibitory role of ZSCNA1 in BC. Mechanistical studies showed that ZSCAN1 directly binds to -951 ~ -925bp region of WWTR1 (encodes TAZ) promoter, inhibits the transcription of WWTR1, thereby inhibiting the stemness of BCSCs. Our work revealed ZSCAN1 as a novel stemness-related tumor suppressor and transcriptional repressor in BC and thus improved our understanding about stemness regulation in BCSCs.